PEMBINAAN KEAGAMAAN PADA PECANDU NARKOBA DI REHABILITASI INSTITUSI PENERIMA WAJIB LAPOR (IPWL) PONDOK PESANTREN SALAFIYAH HIDAYATUL MUBTADI-IEN KOTA BENGKULU - Hendro Cahyana (Manthiq, 2017)
The purpose of this study is an attempt to find out how the method of religious guidance on Drug Addicts at Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien  Bengkulu City. The questions to be answered through this research are: (1) How is the religious activity of santri Drug Rehabilitation Rehabilitation Center at Pondok Pesantren Salafiyah Hidayatul  Mubtadi-ien  Bengkulu  City? (2) How is the  method of religious activity applied  to Drug Addicts in Pondok Pesantren Salafiyah Hidayatul  Mubtadi-ien  Bengkulu  City? (3) What are the barriers  and carrying capacity  an the process of religious guidance on Drug Addicts in Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien  Bengkulu  City